The Influence Of Return On Assets And Growth Of Assets On Dividend Payout Ratio: A Study On Food & Beverage Sub-Sector Companies Listed On The Indonesia Stock Exchange For The Period 2022–2025 - Azmi Fauziah; Uswatun Hasanah; Indri Utami (Institute of Advanced Knowledge and Science, 2026)
This study aims to analyze the effect of Return on Assets (ROA) and Growth of Assets (GA) on Dividend Payout Ratio (DPR) in Food & Beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The study employed a quantitative approach using descriptive and verificative methods. The population consisted of 83 Food & Beverage sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, resulting in 13 companies with a total of 52 observations. The data used were secondary data obtained from annual financial statements and analyzed using panel data regression with EViews 12 software. Based on the Chow Test and Hausman Test results, the most appropriate estimation model was the Fixed Effect Model (FEM). Classical assumption tests included heteroscedasticity and multicollinearity tests. The results indicate that Return on Assets partially has a negative and significant effect on Dividend Payout Ratio with a probability value of 0.0103 < 0.05. This finding suggests that higher profitability tends to reduce dividend distribution because companies prioritize retained earnings for internal financing purposes. Meanwhile, Growth of Assets has no significant effect on Dividend Payout Ratio with a probability value of 0.0866 > 0.05. Simultaneously, ROA and GA variables are able to explain 87.41% of the variation in DPR, while the remaining percentage is influenced by other variables outside the research model.